2017
DOI: 10.1111/bph.13922
|View full text |Cite
|
Sign up to set email alerts
|

Molecular regulation and pharmacological targeting of the β‐catenin destruction complex

Abstract: The β‐catenin destruction complex is a dynamic cytosolic multiprotein assembly that provides a key node in Wnt signalling regulation. The core components of the destruction complex comprise the scaffold proteins axin and adenomatous polyposis coli and the Ser/Thr kinases casein kinase 1 and glycogen synthase kinase 3. In unstimulated cells, the destruction complex efficiently drives degradation of the transcriptional coactivator β‐catenin, thereby preventing the activation of the Wnt/β‐catenin pathway. Mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 171 publications
2
69
0
Order By: Relevance
“…Translocated β-catenin interacts with transcription factor 4 (TCF4) and activates Wnt-targeted genes, which are linked to cell proliferation and apoptosis. [23][24][25] The study of Liang et al revealed that DLX1 binds to β-catenin and enhances the interaction between β-catenin and TCF4. 26 Based on the above information, we hypothesize that DLX1 may regulate cell cycle progression and apoptosis by promoting Wnt signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Translocated β-catenin interacts with transcription factor 4 (TCF4) and activates Wnt-targeted genes, which are linked to cell proliferation and apoptosis. [23][24][25] The study of Liang et al revealed that DLX1 binds to β-catenin and enhances the interaction between β-catenin and TCF4. 26 Based on the above information, we hypothesize that DLX1 may regulate cell cycle progression and apoptosis by promoting Wnt signalling.…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of work has been performed to uncover the intricacies of the signal transduction steps at the cell surface and the cytoplasm to better understand the normal and dysfunctional activity of Wnt signalling. Recent reviews published elsewhere and in this issue describe our current understanding of these steps in detail (Niehrs and Acebron, ; DeBruine et al, ; Driehuis and Clevers, ; Nusse and Clevers, ; van Kappel and Maurice, ; Zimmerli et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Except for the above-mentioned proteins, other proteins, such as Wnt4, ring finger protein 43 (RNF43) [42], zinc and ring finger 3 [43], serine/threonine kinases [44], cellular homologue of myelocytomatosis viral oncogene (c-Myc), the cell cycle regulator D1 (cyclin D1) [45], surviving, Mitogen-activated protein kinase 1 as well as CK1e and traf2and-nck-interacting kinase, have also been discovered to be closely associated with the Wnt signaling pathway, while different proteins appear to play different roles in biochemical signaling mechanisms. Moreover, a series of receptors are also involved in the Wnt/β-catenin pathway.…”
Section: Relevant Proteins and Receptors In The Wnt/β-catenin Pathwaymentioning
confidence: 99%